LAND RIGHTS AND ECONOMIC RESILIENCE OF RURAL WOMEN IN THE G5-SAHEL COUNTRIES, WEST AFRICA - Alfred Runezerwa Bizoza (African Journal on Land Policy and Geospatial Sciences, 2019)
This article discusses different issues pertaining gender and land governance with focus to access and control of land by rural women and how this affects their resilience in G5-Sahel region- Chad, Niger, Burkina Faso, Mali, and Mauritania. Findings show that land remains the property of men, customary chiefs, male members of the family who have the full control of land use; women continue to serve as servants of their husbands in the farming activities. Limited access to production resources such as land, agricultural inputs, small scale irrigation and agricultural mechanization, and lack of post-harvest handling facilities; all restrain women’s economic capacity for their economic resilience to climate change and other natural disasters. There is need, therefore, for innovative models of land tenure regularization systems in the G5-Sahel countries; models that take into account current social, cultural and religious barriers for women’s land access and use for their economic activities.